2021
DOI: 10.1002/ijgo.13496
|View full text |Cite
|
Sign up to set email alerts
|

Association between levator ani avulsion and urinary incontinence in women: A systematic review and meta‐analysis

Abstract: Background Urinary incontinence is a bothersome symptom. Although the relationship between stress urinary incontinence (SUI) and vaginal delivery is established, the pathology underlying SUI after vaginal birth remains to be elucidated. Objectives To determine whether levator ani muscle avulsion predisposes for SUI in women. Search strategy Pubmed and Embase were searched for terms and their variations “levator ani muscle avulsion” and “urinary incontinence”, from inception until 5 November 2019. Selection cri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Smeets, by a systematic review and meta-analysis, has shown that there is no relationship between levator ani muscle avulsion and stress urinary incontinence in women. The diagnosis of levator ani muscle avulsion was made with translabial ultrasound or magnetic resonance imaging in all studies which have been recruited in meta-analysis [26].…”
Section: Resultsmentioning
confidence: 99%
“…Smeets, by a systematic review and meta-analysis, has shown that there is no relationship between levator ani muscle avulsion and stress urinary incontinence in women. The diagnosis of levator ani muscle avulsion was made with translabial ultrasound or magnetic resonance imaging in all studies which have been recruited in meta-analysis [26].…”
Section: Resultsmentioning
confidence: 99%
“…Excessive expansion or prolonged traction will lead to postpartum levator ani injury [ 3 , 15 ]. 3D ultrasound has the advantages of real-time dynamic, high accuracy, repeatable, low price, etc, which can effectively detect the level of maternal LHS and fetal HC with good accuracy [ 16 , 17 ]. Transperineal ultrasound indexes are closely related to the duration of labor.…”
Section: Discussionmentioning
confidence: 99%
“… 44 One systematic review reported a prevalence of stress urinary incontinence in women with levator ani muscle avulsion of 29–69%, at least 1 year after childbirth. 51 Sexual and reproductive health conditions Secondary infertility An analysis of 277 household surveys estimated that the prevalence of secondary infertility was 10·5% (95% CI 9·5–11·7). 52 Postpartum sexual dysfunction (including dyspareunia) A systematic review reported that the overall prevalence of dyspareunia was 35% (95% CI 29–41).…”
Section: The Global Burden Of Neglected Medium-term and Long-term Con...mentioning
confidence: 99%